2018
DOI: 10.3897/zookeys.792.26771
|View full text |Cite
|
Sign up to set email alerts
|

Survey research on the habitation and biological information of Callipogon relictus Semenov in Gwangneung forest, Korea and Ussurisky nature reserve, Russia (Coleoptera, Cerambycidae, Prioninae)

Abstract: An investigation on the habitation of Callipogonrelictus Semenov, 1899 in Gwangneung forest was carried out, where the Korea National Arboretum is located. In an investigation spanning the last eleven years (2007–2017), 22 emergence holes, nine pupal chambers, six adults, and two larvae of C.relictus were identified. In this study, biological information about habitation of C.relictus is provided by comparing and combining the results of this investigation with a survey conducted in Ussurisky Nature Reserve, R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(22 citation statements)
references
References 12 publications
3
19
0
Order By: Relevance
“…-Introduction of C. relictus with pictures of Chinese specimens and individuals in breeding. Lee et al (2018) -Report of the results of an investigation of C. relictus in Gwangneung Forest from 2007-2017 -Comparison of results from Gwangneung Forest, Korea and Ussuri Nature Reserve, Russia -New distribution record: Yangyang-gun, Gangwon Province. Lee et al (2019) -New host record of C. relictus: Quercus aliena Blume -Summary of host species (17 species of 11 genera in seven families) of C. relictus from Korea, China, and Russia.…”
Section: Referencementioning
confidence: 99%
See 3 more Smart Citations
“…-Introduction of C. relictus with pictures of Chinese specimens and individuals in breeding. Lee et al (2018) -Report of the results of an investigation of C. relictus in Gwangneung Forest from 2007-2017 -Comparison of results from Gwangneung Forest, Korea and Ussuri Nature Reserve, Russia -New distribution record: Yangyang-gun, Gangwon Province. Lee et al (2019) -New host record of C. relictus: Quercus aliena Blume -Summary of host species (17 species of 11 genera in seven families) of C. relictus from Korea, China, and Russia.…”
Section: Referencementioning
confidence: 99%
“…Callipogon relictus was recorded from China, Russia and the Korean Peninsula (Byun et al 2007;Li et al 2013;Bezborodov 2016;Yi et al 2018). Its disjoint distribution is considered evidence of a connection between the Old World and the New World by the Bering landbridge (Kuprin and Bezborodov 2012;Lee et al 2018). showed that Callipogon originated in the Paleocene ca.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The longhorned beetle genus Callipogon Audinet-Serville, 1832 [ 1 ] (Coleoptera: Cerambycidae) consists of five subgenera including nine species worldwide. Only a single species is found in East Asia (Korea, China, Far Eastern Russia), while the remaining species are distributed across Central and South America, including Mexico, Guatemala, and Colombia [ 2 , 3 ]. The relict longhorn beetle Callipogon relictus Semenov, 1898 [ 4 ] is the sole Asian representative of the genus, and thus represents one of most intriguing insects in the Palearctic region, both in terms of its biogeographical and ecological history, as well as its unequivocal importance for conservation.…”
Section: Introductionmentioning
confidence: 99%